1991
DOI: 10.1007/bf02307317
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of intercellular communication by airborne particulate matter

Abstract: To investigate the inhibition of gap junction mediated intercellular communication (IC) by extracts of airborne particulate matter (APM), V79 cells were incubated with extracts of APM and subsequently microinjected with the fluorescent dye Lucifer Yellow, after which the number of fluorescent (= communicating) cells was determined. To compare inhibitory effects on IC with mutagenicity, APM was also tested in the Salmonella microsome assay. Six different extracts were tested, two outdoor extracts representing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Combining these results with those of the genotoxicity assays, it can be concluded that nitrosated 4-chloroindoles should be considered as potential genotoxic agents and agents with potential tumor-promoting capacity. The capability to inhibit GJIC had previously been reported for only a few other genotoxic chemicals or mixture of chemicals such as dimethylbenzanthracene (Jongen et al, 1987), cigarette smoke condensate (Jongen et al, 1985), and airborne particulate matter (Heussen, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Combining these results with those of the genotoxicity assays, it can be concluded that nitrosated 4-chloroindoles should be considered as potential genotoxic agents and agents with potential tumor-promoting capacity. The capability to inhibit GJIC had previously been reported for only a few other genotoxic chemicals or mixture of chemicals such as dimethylbenzanthracene (Jongen et al, 1987), cigarette smoke condensate (Jongen et al, 1985), and airborne particulate matter (Heussen, 1991).…”
Section: Discussionmentioning
confidence: 99%